Lin-Manuel Miranda: Hamilton, a New Era of Broadway Musicals - Besmir Shishko (Thesis, 2019)
Over the past two years, something odd has happened on Broadway, which can be accredited to one man, or rather two. A new musical known as Hamilton, based on the genius and life of Alexander Hamilton, is striving to become one of the most beloved, most viewed and widely appreciated Broadway shows of all time, and it is all the creation of Lin Manuel Miranda. This paper aims to address the issues of changing the conventional Broadway music by introducing hip-hop, which seemingly focuses on rapping about relevant issues over edgy beats. In line with relevant literature, the dissertation attempts to explore the role of the introduction of modern hip-hop music and diverse cast playing the protagonist parts of the Founding Fathers in achieving to convey the message of Hamilton while changing the face of orthodox Broadway plays. The paper departs from the question of whether these elements are successful in attracting diverse ethnicities and a younger audience, while simultaneously managing to gross higher ticket sales.